Bilateral Ovarian Endometriomas Presenting as Nonprogress of Labor: First Case Report in the Literature Is Concomitant Surgical Excision during Cesarean Section Advisable? - Shashank Shekhar; Chanderdeep Sharma; Vinay Somya; Meghna Thusoo; Nidhi Raina (Hindawi Limited, 2012)
Objective. To report the first case of bilateral ovarian endometriomas, leading to nonprogress of labour, successfully excised during cesarean section. Design. Case report. Setting. Department of Obstetrics & Gynecology of Dr. RPGMC Tanda, Kangra, India. Patients. A primigravida in labour at term gestation. Interventions. Surgical management. Main Outcome Measures. Description and treatment of a pregnant woman with bilateral ovarian endometriomas during cesarean section. Results. Successful excision of ovarian endometriomas and reconstruction of the ovaries during cesarean section. Conclusion. Management of incidentally detected endometriomas during cesarean section should be individualized, taking into account the symptoms, size, bilaterality, and adhesion with adjacent organs.